Projection of nursing profession in Malaysia: where we are and what need to be improved? - Sowtali, Siti Noorkhairina (Medwin Publishers, 2019)
Nursing profession in Malaysia has gone through several paradigm shift since it began in early 19th century. At that particular time, hands-on approach is the medium of educating the young nurses adopted by the British doctors and nurse supervisors. Later on, the academia world of Nursing profession had evolved into several stage of qualification offerings such as Diploma/Advance Diploma, Degree/Bachelor, Master and Doctor of Philosophy to fulfill the requirement stipulated by the Ministry of Health, Malaysia Qualification Assurance and Ministry of Higher Education. This is in line of becoming a developed nation whereby there is a need to produce more postgraduate holder and research study in critical area which includes Nursing. Therefore, nurses role are now expand not only limited to clinical setting but require various expertise in academic, research and top division management of the Nursing profession. Thus, there is a need to recruit more male nurses, creating a clinical nurse specialist post to avoid ‘brain drain’ of the geniuses and to reduce burnout issues among Malaysian nurses. More support and supervision from the universities or colleges’ management is needed especially to motivate the nurses with Master and Doctor of Philosophy to get involve in research and publication since the acceptance is still at low or moderate level in certain institutions. Since nurses are the heart of the healthcare team with multitasking role, there is also a need to look upon their welfare by various responsible organizations in the future.